Integrity testing and the prediction of counterproductive behaviours in the military. Issue 1 (18th April 2015) - Fine, Saul; Goldenberg, Judith; Noam, Yair
Abstract : While a great deal of research has been carried out on counterproductive work behaviours and integrity testing in civilian organizations, far less is known about these two areas in military settings. The present study developed a military‐oriented integrity test that successfully predicted future disciplinary infractions among a sample of 467 officer training school candidates (ρ = .26), while also discriminating between that sample and a comparable sample of soldiers serving time in military prisons ( d  = 2.24). In addition to its unique military setting, this study contributes to the integrity test literature by: (1) adopting both individual‐ and group‐level validity paradigms; (2) using a sample of actual job applicants; (3) measuring a reliable objective criterion in a predictive design; and (4) including comparative measures of cognitive ability, personality, and overall assessment centre ratings. Practitioner points: Military settings may uniquely facilitate the reliable and objective measurement of counterproductive work behaviours. Integrity testing may be a valid and incremental predictor of counterproductive behaviours in military settings.